Pembuatan Aplikasi Sebagai Penanda Mengenai Kampung Kreatif Tematik Pada Smart Branding Kota Bogor Berbasis Android - Rusdian, Raden Agung Pradhana; Prasetyo, Agung Budi (JoMMiT, 2020)
The City of Bogor began to develop programs related to Smart City so that city management could run more easily with the help of technology. Bogor City made 6 dimensions in Smart City namely Smart Governance, Smart Branding, Smart Economy, Smart Living, Smart Society, and Smart Environment. One of the Offices related to the construction of the Bogor City Smart City is the Office of Communication and Information, Bogor City Encoding or commonly called Diskominfo. One of the developments is to make a media marker about tourist attractions, namely thematic creative villages. But the media is not enough to make people more interested and want to find out more deeply. That way, this navigation application is needed to complement the information media to be more interactive and have more value. The advantage of this application is that it can bring up virtual panoramic objects and also a location map that makes it easy for tourists to know the location to be addressed. This application is designed for Android-based Smartphones with a minimum specification KitKat.